Effect of Carthamus Tinctorius Safflower Aqueous Extract Against Nickel Chloride Induces Hematotoxicity and Immunotoxicity in Adult Male Rabbits - Sadiq Laylani, Layla Abd-Al-Sattar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was designed to show, the role of Carthamus tinctorius safflower aqueous extract against toxicity of nickel chloride (NiCl2). Twenty male, rabbits were used and divided into four groups (with 5 rabbits in each group); group (control group) received normal diet, group II received orally 100mg/kg NiCl2 for six weeks, group III received 100mg/kg NiCl2 and 100mg/kg extract six weeks, group IV received 100mg/kg NiCl2 and 200mg/ kg extract six weeks. Hematological parameters showed (RBC (Red blood cells), Hb (Hemoglobin), PCV (Packed cells volume) decreased and WBC (White blood cells) increased) significant changes (P < 0.05) compared with control group. Immunological parameters (IgG, IgA and IgM increased) and oxidative stress factors (MDA increased and GSH decreased) show significant changes (P < 0.05) compared with control group. While, safflower aqueous adverse the negative effects of NiCl2 and causing ameliorative effects on all hematological parameters, hematological immunological parameters and oxidative stress factors showed no significant changes (P < 0.05) compared with control group. It was concluded that flower extract of Carthamus tinctorius has been antioxidant role against nickel chloride toxicity in rabbits.